PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM MENGATASI KESULITAN BELAJAR BAHASA INDONESIA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Nurhudayana Ridwan; Irwan Akib; Rukli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to overcome the problem of student learning difficulties through the application of differentiated learning in class IV elementary school students. The type of research that used is qualitative research with observation as data collection techniques. The subject used is 19 students with qualitative descriptive analysis technique. The results of the study show that the application of differentiated learning in Indonesian language learning is evident to overcome the learning difficulties experienced by students. The findings of this study is the importance for teachers to carry out cognitive and non-cognitive diagnostic assessments to determine the learning needs of each student.